Revival of Legacy of Tooke and Gibson: Implications for Monetary Policy - Atiq-ur-Rehman (Journal of Central Banking Theory and Practice, 2015)
The monetary policy rules used by central banks these days are based on the assumption that inflation could be reduced by increasing interest rate. On contrary, Tooke (1774-1858), the forefather of monetary economics, was of the view that the relationship between interest rate and inflation should be positive. His view was based on simple logic, `interest is a part of cost, and therefore, the increase in interest rate should increase inflation by increasing cost of production (Tooke, 1838)'. Tooke's view has got support from a number of empirical evidence including Gibson (1923) who found positive correlation between two variables for UK data over a period of 200 years. On the other hand, mainstream economic thinking on which the actual monetary practices are based ignored any possibility of positive relationship between interest rate and inflation throughout the history. The existence of Tooke's cost side effects of monetary policy is a serious concern because if these effects exist than the use of monetary policy would be counterproductive. Using the data from entire globe, I attempt to explore the nature of relationship between the interest rate and inflation. I found that the data supports the perception of Tooke and Gibson and denies that the effectiveness of monetary policy currently adapted by the correlation between interest rate and inflation is positive. The results are robust to sample size, sample period, and various definitions of interest rate and inflation.
Keywords: E40; E42; E52; 330; Cost Channel; Gibson Paradox; Tooke Banking School Theorys